2008
DOI: 10.1016/j.tins.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Limbic and cortical information processing in the nucleus accumbens

Abstract: The nucleus accumbens regulates goal-directed behaviors by integrating information from limbic structures and the prefrontal cortex. Here, we review recent studies in an attempt to provide an integrated view of the control of information processing in the nucleus accumbens in terms of the regulation of goal-directed behaviors and how disruption of these functions might underlie the pathological states in drug addiction and other psychiatric disorders. We propose a model that could account for the results of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
237
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(254 citation statements)
references
References 59 publications
12
237
1
4
Order By: Relevance
“…As noted above, reciprocal innervation is evident also, and stimulating the afferent fibers from the amygdala and hippocampus increases accumbal DA release (Floresco et al, 1998;Floresco et al, 2001). Our finding of DA responses to cocaine cues in all three regions-amygdala, hippocampus, and striatum-supports the view of limbic and striatal structures as components of an integrated system, contributing to the incentive salience of motivationally relevant cues Phillips et al, 2003;Goto and Grace, 2008;Shohamy and Adcock, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As noted above, reciprocal innervation is evident also, and stimulating the afferent fibers from the amygdala and hippocampus increases accumbal DA release (Floresco et al, 1998;Floresco et al, 2001). Our finding of DA responses to cocaine cues in all three regions-amygdala, hippocampus, and striatum-supports the view of limbic and striatal structures as components of an integrated system, contributing to the incentive salience of motivationally relevant cues Phillips et al, 2003;Goto and Grace, 2008;Shohamy and Adcock, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…The amygdala is thought to have an important role in the acquisition and expression of learned associations between emotionally important events. In conjunction with activity in the striatum and hippocampus, these effects influence the ability of motivationally salient stimuli to elicit and sustain focused interest and facilitate the selection of situation appropriate behavioral responses Phillips et al, 2003;Goto and Grace, 2008;Robbins et al, 2008;Shohamy and Adcock, 2010). In humans, the role of the amygdala in the processing of emotionally relevant stimuli has been studied using various methods, including functional neuroimaging (Chase et al, 2011;Tang et al, 2012), assessments of the effects of naturally occurring selective lesions (Adolphs et al, 1995;Tsuchiya et al, 2009), and following direct electrical stimulation (Rayport et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is well supported by previous evidence of the existence of projections from orbitofrontal cortices to the NAcc in primates (Haber et al, 1995). Furthermore, the functional interaction of orbitofrontal cortices and mesolimbic dopaminergic brain areas has already been described in experimental animals (Carr and Sesack, 2000;Goto and Grace, 2008). In humans, an exaggerated fMRI signal of the NAcc relative to lateral orbitofrontal activity has been shown in adolescents.…”
Section: Discussionsupporting
confidence: 75%
“…Preclinical studies have shown that increased serotonergic tone under SSRIs may facilitate dopaminergic activity under some circumstances, but dopamine release in the nucleus accumbens (NAcc) decreases via stimulation of serotonergic 5HT2C receptors (Alex and Pehek, 2007). Downregulation of reward processing under SSRIs furthermore may relate to reciprocal interactions of prefrontal areas with the NAcc (Carr and Sesack, 2000;Goto and Grace, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been suggested that a phasic DA release evoked when an animal encounters unexpected reward facilitates the hippocampal drive of nucleus accumbens neurons through action on D1 receptors. In contrast, a suppression of DA release could decrease tonic DA stimulation of D2 receptors and, in turn, input integration in the nucleus accumbens is shifted favoring prefrontal over hippocampal signals (Goto and Grace, 2008). Correspondingly, contingency degradation as tested here represents a situation involving an unexpected transition of the predictive value of the context.…”
Section: Discussionmentioning
confidence: 92%